Knowledge, Skills, and Perceived Competency in Handling Medical Emergencies among Dental House Officers and General Dentists: Knowledge, Skills, and Perceived Competency in Handling Medical Emergencies - Anwar, Malik Adeel; Rehman, Ijaz Ur; Khalil, Fatima; Saeed, Tooba; Shakeel, Sadia; Arif, Khadija; Kushef, Hooria (Pakistan Journal of Health Sciences, 2024)
Dental practitioners frequently encounter medical emergencies due to the nature of their work and the inherent stress within a dental office. Adequate preparation and confidence in handling such emergencies are very important for patient safety. Objectives: To assess the knowledge, skills and perceived competency of house officers and general dentists in managing medical emergencies in dental practice. Methods: A cross-sectional survey was conducted in Lahore among house officers and general practitioners. The survey included a pre-valid questionnaire on medical history documentation, attendance at medical emergency workshops, confidence in performing cardiopulmonary resuscitation, administering intravenous drugs, and managing common emergencies like syncope and hypoglycemia. Statistical analysis was performed with Chi-square and Fisher’s exact tests applied to assess associations. Results: The majority of participants demonstrated adequate knowledge of medical emergency protocols, with 68% aware of the need to record medical history and 73% familiar with universal precautions. However, 45% reported being trained in administering cardiopulmonary resuscitation and 29% in administering intravenous drugs. Confidence in handling emergencies such as syncope (0.004) and unconscious hypoglycemic patients (p-=0.03) was significantly higher among dentists with more experience. Conclusions: It was concluded that while dental practitioners generally possess knowledge about medical emergency protocols, there is a gap in training and confidence particularly in administering lifesaving procedures. More experienced dentists demonstrated higher confidence compared to house officers.